PERTANGGUNGJAWABAN HUKUM PELAKU TINDAK PIDANA PERJUDIAN SLOT ONLINE DI INTERNET (STUDI PUTUSAN NO 472/PID.B/2024/PN PSP) - Candra Nurhayati Pertiwi; Indah Sari (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
Gambling is a social disease that has hit society everywhere, including the people of Demak Regency. In general, gambling is a form of game using bets that are based on luck, to win also requires playing skills. Gambling in the historical process has not been easy to eradicate, although the reality also shows that the gambling proceeds obtained by the government can be used for development efforts, but apart from that the negative impact of gambling is greater than the positive impact. Criminal law is often used to solve social problems, especially in overcoming crime. Especially the problem of gambling as a form of social disease. The problem is formulated as follows: How is the implementation of criminal sanctions for perpetrators of gambling crimes in the Padang Sidempuan District Court?, Is Decision No. 472 / Pid.B / 2024 / PN.PSP in accordance with the laws and regulations or not. Gambling crimes are regulated in the Criminal Code Law (Lex Generalis) and Law Number Information and Electronic Transactions (Lex Specialis).